2012
DOI: 10.1007/s00234-012-1083-z
|View full text |Cite
|
Sign up to set email alerts
|

Value of diffusion-weighted imaging in central pontine and extrapontine myelinolysis

Abstract: We conclude that early DWI changes are a common finding in CPM/EPM but do not regularly precede tissue changes detectable on conventional MRI sequences. Heterogenous ADC values possibly represent different stages of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
6

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
0
31
0
6
Order By: Relevance
“…In this case, brain MRI images corresponded with typical radiological findings of CPM and extrapontine lesions were showed the same results. One study reported that early DWI changes are a common finding in ODS but do not regularly precede the tissue changes that are detectable on conventional MRI sequences [2]. With these radiologic findings, neurologic examinations, laboratory findings, and past history, we finally diagnosed ODS and could differentiate from other possible diseases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this case, brain MRI images corresponded with typical radiological findings of CPM and extrapontine lesions were showed the same results. One study reported that early DWI changes are a common finding in ODS but do not regularly precede the tissue changes that are detectable on conventional MRI sequences [2]. With these radiologic findings, neurologic examinations, laboratory findings, and past history, we finally diagnosed ODS and could differentiate from other possible diseases.…”
Section: Discussionmentioning
confidence: 85%
“…CPM is classically described as the radiological manifestations of osmotic myelinolysis, and clinical symptoms range from subtle changes in cognitive functions to life-threatening autonomic and brainstem dysfunction and death [1]. EPM develops in extrapontine sites through mechanisms similar to CPM but the cases of EPM have been reported rarely than those of CPM [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic myelinolysis classically occurs in the setting of rapidly corrected severe hyponatremia of several days duration [94]. Conditions associated with osmotic myelinolysis include alcoholism, alcohol withdrawal, malnutrition, liver transplantation, cirrhosis and severe burns [95]. Prognosis is quite variable, with approximately one-third of patients recovering completely, onethird having mild residual neurologic deficits and one-third remaining severely neurologically impaired [96].…”
Section: Osmotic Myelinolysismentioning
confidence: 99%
“…In some studies, diffusion abnormalities were seen days to weeks before abnormalities appeared on conventional MRI sequences [98]. Over the course of weeks, the diffusion abnormalities may completely resolve or demonstrate T 2 shine-through [95,98,99]. Resolution of diffusion abnormalities may predict a better prognosis for the patient [99], although this is controversial [96].…”
Section: Osmotic Myelinolysismentioning
confidence: 99%
See 1 more Smart Citation